2014
DOI: 10.5435/jaaos-22-12-810
|View full text |Cite
|
Sign up to set email alerts
|

Elbow Arthroscopy

Abstract: Elbow arthroscopy is a tool useful for the treatment of a variety of pathologies about the elbow. The major indications for elbow arthroscopy include débridement for septic elbow arthritis, synovectomy for inflammatory arthritis, débridement for osteoarthritis, loose body extraction, contracture release, treatment of osteochondral defects and selected fractures or instability, and tennis elbow release. Contraindications, technical considerations, and favorable outcomes following treatment with elbow arthroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…In the study of Marti et al, osteoarthritis, stiffness, and foreign body of elbow joint were the most common indications of elbow arthroscopy (8). Also, Adams et al reported that the most common indications of elbow arthroscopy were debridement of septic arthritis, synovectomy in elbow inflammation, osteoarthritis debridement, and treatment of osteochondral defects (13).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the study of Marti et al, osteoarthritis, stiffness, and foreign body of elbow joint were the most common indications of elbow arthroscopy (8). Also, Adams et al reported that the most common indications of elbow arthroscopy were debridement of septic arthritis, synovectomy in elbow inflammation, osteoarthritis debridement, and treatment of osteochondral defects (13).…”
Section: Discussionmentioning
confidence: 99%
“…Also, Adams et al expressed that arthroscopy is an appropriate procedure for treatment of inflammatory arthritis, osteoarthritis, and lateral epicondylitis (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other complications could be the presence of fistulae or the necessity of persistent drainage and neurovascular damage. The latter is quite difficult to avoid and commonly involves the ulnar nerve, followed by the superficial radial nerve, posterior interosseous nerve, anterior interosseous nerve, and medial antebrachial cutaneous nerve [53]. Interpositional arthroplasty represents an alternative to total elbow arthroplasty (TEA) in young adults [54].…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…1,2,28 Prior literature suggests that greater than 75% of the capitellum can be accessed through a dual lateral approach. 13 However, no studies have compared the accessibility of the capitellum from other popular posterior portals such as the posterolateral and distal ulnar portals.…”
mentioning
confidence: 99%